Analisis Pencucian Logam Berat Merkuri (Hg) Daging Ikan Patin Siam (Pangasianodon hyphopthalmus ) Sungai Batanghari Melalui Pemberian Pakan Komposisi Asam Sitrat - Syahrizal Syahrizal; Safratilofa Safratilofa; Sutrisno Sutrisno (Jurnal Akuakultur Sungai dan Danau, 2022)
Citric acid is a weak organic acid found in citrus fruits and leaves with many benefits. This study aimed to examine the effect of citric acid in feed on the leaching of heavy metal mercury (Hg) from the body of the catfish (Pangasianodon hypophthalmus). This research was conducted in a semi-indoor room. The research design used a completely randomized design (CRD) with 4 (four) treatments and 2 (two) replications. Treatment A (0.0 gram/kg), B (1.0 gram/kg), C (2.0 gram/kg) and D (3.0 gram/kg). The test fish were catfish with a weight of ±266.03 grams/head. Catfish obtained from the Batanghari river taken from cultivators in Sebubuk Village, Muaro Jambi, immediately the Hg levels in catfish meat ranged from 0.000021- 0.000038 µg/gram in waters that had Hg levels of 0.00018 µg/ml. Then the fish were kept in a concrete tank measuring 70x40x35 cm as many as 8 units with a volume of 200 liters of water. The test feed was given satisfactorily three times a day. The results of observations of citric acid feeding for 40 days showed that the Hg of early catfish meat on the back g/gram 0.000035 µg/gram was higher than in the stomach 0.000032 µg/gram and tail 0.000020 µg/gram. The results of the analysis between treatments of fish meat Hg were significantly different and there was a decrease in Hg levels, for treatment A 0.000032 to 0.000025, B 0.000031 to 0.000024, C 0.000030 to 0.000022 and D 0.000029 to 0.000020 µg/gram. The average decrease in Hg of meat was 0.00000305 to 0.00000228 µg/gram. The best average survival rate of catfish in treatment D (100%) and the lowest A (75%).